Developing a cost statement framework for SMEs: a tool to enhance selling price prediction and profitability - Razak, Syuhaila; Nik Wan, Nik Zam; San, Suzana; Saidi, Noraida (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Small and Medium Enterprises (SMEs) struggle to set the right selling prices because they can't access complex costing tools and methods. This project introduces a practical and user-friendly cost statement framework designed specifically to help SMEs predict selling prices effectively. By breaking down fixed costs, variable costs, and overheads, the framework makes simpler cost allocation and provides a clear structure for determining profit margins. This revolution integrates basic accounting principles with predictive analytics to support data driven decision- making. Additionally, the framework offers customization options to cater to different industries, ensuring significance and flexibility. The goal is to enable SMEs with the tools needed to improve pricing strategies, improve financial performance, and gain a competitive edge in the market. By bridging the gap between traditional cost management practices and modern pricing needs, this project provides a cost-effective solution to adopt business growth and sustainability.